Bear: o que acontece quando uma webcomic migra para o papel - Gambarini, Klaus Wagner Saglauskas [UNIFESP] (2019)
The objective of the present research is to verify what happens when a comic book migrates from the digital support to the print version. Just as we intend to understand how the reader forms the meanings of the text, what changes the author needs to make to fit the work in the support migration process, comparative analysis of a comic in both supports and evidence the importance for the language of the comics. To do this study, the corpus chosen was the comic “Bear”, by Brazilian author Bianca Pinheiro, who originaly created as "BEAR, webcomic por Bianca Pinheiro" in 2012 and migrated support for the print books “Bear”, Volumes 1, 2 and 3. The clipping will be the Prologue and Chapter 1 of webcomic and Volume 1, released in book. The papers presents as theoretical basis the definitions of support of Debray (1993), Marcuschi (2003, 2018), Maingueneau (2013), Bonini (2011) and Távora (2008, 2012). For the definition of webcomics and digital comics, it will be used as theoretical studies by Cirne (1972), Franco (2007, 2008, 2013), Mendo (2008), Ramos (2009), Santos (2010), Veronezi (2010). Eisner (2010), Luna (2013), Cagnin (2014), Groensten (2015) and Barbieri (2017). To analyze or process the webcomic process for printing, comparisons will be made between frames and corresponding pages in two different sports. We seek to understand how the reader forms or the meaning of the narrative by means of tracing in the text using as theories of the Textual Linguistics of Koch (2008, 2016, 2017), Marcuschi (2003, 2018), Cavalcanti (2012) and Koch and Elias (2016). ). One hypothesis is that when migrating from support, a comic book presents different tracks to the reader so that the senses of the text. With no technological capability for mass interaction or animation, paper requires manipulation in the original text.